Predictive value of brain natriuretic peptide for cardiovascular risk assessment in non-cardiac surgery - O. N. Dzhioeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The incidence of postoperative complications has decreased significantly over the past 30 years, but the consequences after surgery are still a serious clinical problem. Identifying intra- and postoperative myocardial injury is a challenging task, since almost half of all complications occur in patients who were not initially at high risk without a history of heart disease. Currently, several large studies and meta-analyzes over the past 5 years recommend the determining brain natriuretic peptide (BNP) levels for risk stratification in all patients scheduled for elective non-cardiac surgery in order to improve the postoperative outcome. Monitoring of BNP level during the entire perioperative period can contribute to a better understanding of the pathophysiology of cardiac complications in noncardiac surgery. The introduction of new criteria will qualitatively improve care to patients with comorbidities, reduce the number of postoperative complications and improve interdisciplinary interactions of specialists.